Problem-Solving and Computational Thinking Practices: Lesson Learned from The Implementation of ExPRession Model - Natalya Limbong; Kartini Herlina; Hervin Maulina; Abdurrahman Abdurrahman (STKIP Singkawang, 2023)
Computational thinking ability is one of today's problem-solving methods that can be applied in physics learning. However, it is not yet known by most teachers so it has not been applied optimally in learning activities. This study aims to identify students' problem-solving and computational thinking abilities in solving well-structure physics problems. The subject of this study was the eleven grade majoring in natural science of SMAN 1 Bangunrejo. This type of research is descriptive research. The data used to analyze the students' problem-solving and computational thinking abilities were obtained from the essay test. Based on the results of descriptive analysis, it can be concluded that there is a relationship between students' problem-solving abilities and students' computational thinking abilities. In making a useful description, abstraction and decomposition abilities are needed, while to determine the physics approach and specific application of physics, generalization abiliy are needed. In solving mathematical procedures, algorithm ability are needed and to find out logical progressions, debugging ability are needed.